DETERMINANT OF THE INCIDENCE OF PULMONARY TUBERCULOSIS - Yetiani, Novin (JOURNAL OF RESEARCH IN PUBLIC HEALTH SCIENCES, 2019)
Tuberculosis is an infectious disease that is mostly caused by the bacteria mycobacterium tuberculosis. Patients with pulmonary tuberculosis with smear (+) in Tanjung Puri health center, namely, in 2014 there were 30 patients, in 2015 there were 25 patients, and in 2016 there were 35 patients but 15 of them were declared cured. The purpose of this study was to determine the determinants associated with the incidence of pulmonary TB. This type of research is quantitative research with the type of case control research. The total population is 60 respondents with the number of cases as many as 20 people and controls are people who have the same criteria as the case of 40 people. Samples were taken by purposive sampling technique. Data analysis using statistical software with a significant level of 0.05. The results of statistical tests showed no relationship to the incidence of pulmonary tuberculosis (p=1,000), there was a relationship of knowledge with the incidence of pulmonary TB (p=0.022 and OR=4,500), there was a relationship with the incidence of pulmonary TB (p=0.008 and OR=6,000 ), there is a relationship between the environment and the incidence of pulmonary TB (p=0.036 and OR=3.889). It is recommended that health workers be able to provide counseling to the community so that they can implement their behavior in a clean and healthy life.